Mathematical analysis of hepatitis C model for intravenous drug misusers: Impact of antiviral therapy, abstinence and relapse. (May 2014) - Mushayabasa, Steady; Bhunu, Claver P
Despite advances in hepatitis C therapy and better knowledge of viral/host factors related to disease progression, hepatitis C virus (HCV) remains the leading cause of chronic liver disease, causing progression to end-stage liver disease (ESLD) as well as the development of hepatocellular carcinoma. In this paper a mathematical model for assessing the impact of antiviral therapy, abstinence and relapse on the transmission dynamics of HCV is formulated and analyzed. A threshold quantity known as the reproductive number has been computed, and the stability of the steady states has been investigated. The dynamical analysis reveals that the model has globally asymptotically stable steady states. The impacts of antiviral therapy, abstinence and relapse on the transmission dynamics of HCV are discussed through the basic reproductive number and numerical simulations.